The velveteen rabbit with annotations - Wurfel, Marlene (My University, 2020)
This beautiful story written in 1922 by Margery Williams is almost 100 years old and about a time in history before there was antibiotic treatment for scarlet fever, a potentially fatal childhood disease. It's a story not only about survival, but resilience, change, love, and fairy magic. Read and annotated by Marlene Wurfel. Licences and Attributions: The Velveteen Rabbit by Margery Williams (1922) is part of the public domain. Music: Gymnopedie No.1 by Kevin MacLeod, Meditation Impromptu No.2 by Kevin MacLeod and Heartbreaking by Kevin MacLeod under a Creative Commons Attribution license via the YouTube Audio Library: https://www.youtube.com/audiolibrary/music?nv=1 (https://creativecommons.org/licenses/by/4.0/) Source: http://incompetech.com/music/royalty-free/index.html?isrc=USUAN1100787 Artist: http://incompetech.com/ Birdsong sample by juskiddink on https://freesound.org/ via a creative commons license https://creativecommons.org/licenses/by/3.0/ & Fantasy Windchimes by Northern87 on https://freesound.org/.
Keywords: storytelling; children's stories